Hal-Hal yang Berhubungan dengan Demam Berdarah Dengue pada Penderita di Wilayah Indonesia Periode Tahun 2015 sampai dengan Tahun 2020 - Tammu, Yefta Mandoa; Nurliana, Nurliana; Rahmadani, Andi Anissa (Bosowa Medical Journal, 2024)
Dengue Hemorrhagic Fever is a disease transmitted by Aedes mosquitoes that occurs in tropical and subtropical regions with the main source of transmission being human sufferers. This study aims to analyse things that related to dengue hemorrhagic fever patients in Indonesian region from 2015 to 2020. Research method used analytical research by processing the result obtained from nine scientific research journals with case control design. The result from nine scientific research journals founded that there were significant correlation between dengue hemorrhagic fever with educational level (0,013), repellent (0,005), and hanging clothes (0,003). From this research concluded that educational level, repellent, and hanging clothes are related to dengue hemorrhagic fever.